Lawfare in Ecuador: Impact for communication and society in a context of Elections and political conflicto - Vélez Vélez, Jorge Erwin (Scripta Mundi, 2024)
Lawfare in Ecuador has been a political strategy used to delegitimize opponents and manipulate public opinion, affecting freedom of expression and information transparency. This phenomenon has generated a profound destabilization in social cohesion, especially in electoral contexts, where justice and the media have been instrumentalized to persecute politicians. In addition, it has contributed to the institutional weakening and increase in political violence, as evidenced by the murder of a presidential candidate in the 2023 elections. This review seeks to offer a critical analysis of the impact of Lawfare on Ecuadorian democracy. Objective: Analyze how Lawfare has been used as a political strategy, its consequences for freedom of expression, transparency in information, and its destabilizing effect on social cohesion. Materials and Methods: This review article is based on a qualitative approach, using a bibliographic-documentary review methodology under the positivist paradigm. 35 articles, 10 books and 5 audiovisual materials were collected and analyzed, selected for their relevance in the study of Lawfare in Ecuador and Latin America. The information was processed using tools such as Excel, Word and ATLAS ti, prioritizing recent and exhaustive studies that address the impact of Lawfare on the media, political culture and electoral processes.
Keywords: Keywords: Communication, Society, Lawfare, Politics, Democracy